PELAKSANAAN KEWAJIBAN ORANG TUA TERHADAP ANAK PECANDU GAME ON-LINE DI JALAN SALAK RAYA KOTA BENGKULU DALAM PERSPEKTIF HUKUM ISLAM - Firdaus, Julian (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
In this research  there  are several  problems  1). How the rights and  obligations  of parents  to children  online  game addicts. 2). How to review Islamic law against children online game addicts at Warnet BM Jalan  Salak Raya, Bengkulu City. To answer  the problem  of research  above  conducted field research  (field research)  using qualitative  descriptive approach method. The data  collected by observation method, interview and documentation, from the source of the informant  that the author  set based  on purposive sampling.  The results of the study explain,  first Rights and  obligations  of parents  to the child has not been done  due to various factors, among  others,  busy work so that the lack of attention to children who cause  children abandoned. Second  Every child should  be good  and  obedient to the parents. The child is not justified in being  abusive  to both  parents. Therefore, every child must have  obligations  and  responsibilities  to parents  who have  raised  and  nourished them  from child- hood  to adulthood. Children should keep the rights of parents, children should also maintain morals as stock in running  Ikhsan against both parents